SOSIALISASI PENGENALAN KEWENANGAN LEMBAGA MAHKAMAH KONSTITUSI DI SEKOLAH DASAR - N.A. Aryani; Ibrahim R; I.G.A.M.R. Jayantiari; A.A.S. Indrawati; N.M.D.R. Rani; N.P.Y.K. Dewi (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2024)
The purpose of this service is to socialize the importance of introducing the constitution at an early age, in this case focusing on state institutions both before and after the amendment to the 1945 Constitution of the Republic of Indonesia. One of the new state institutions that emerged after the amendment was the Constitutional Court. The Constitutional Court has the main function of being the guardian of the constitution, which is interpreted as an actor of judicial power who has the dignity to ensure that the constitution, as the highest law, can be enforced properly. From the description above, there are 2 (two) problems, namely: (1) what is the position of the Constitutional Court in the constitutional structure in Indonesia, and (2) how is introduced at an early age, especially the authority of the Constitutional Court institution at Elementary School Number 3 Padangkerta, Karangasem.The target is for the students to understand the constitution from an early age, which of course is adjusted to the level of education, and have the ability to distinguish each authority or obligation of the Constitutional Court. The methods used in this service are lectures, discussions, and questions and answers, as well as providing direct examples related to the decisions. The result of this service is that students get a comprehensive picture of the authority of the Constitutional Court. Keywords: Authority, constitutional court, institution, socialization.